I feel like you should have been given more information than what's been shown to us
a = 12, b = 2, c = 11
Using exponent rules we can distribute the exponent of 3 to the xyz.
This results in the numerator now being. This can be simplified to, .
Now divide the numerator by the denominator subtracting the exponents.
So a = 12
b = 2
c = 11
a = 12, b = 2, z = 11
=> a = 12
=> b = 2
=> z = 11
x^12 y^2 z^11
On the numerator you distribute the exponent 3 to the other exponents.
I think you multiply the 3 so you would get: x^15 y^3 z^12.
so it looks like x^15 y^3 z^12 / x^3yz
Then you subtract the top exponents from the bottom exponent because when you are dividing you subtract exponents. the exponent for y and z in the denominator is 1
and thats how i got x^12 y^2 and z^11. The exponents are a b and c
I hope that is right
Next simplify the fraction this is done by subtracting the powers so x^15y^3z^12/x^3yz =x^12y^2z^11 (because any singular letter term ie y can also be seen as y^1, using this 15-3=12, 3-1=2, 12-1=11) this is your final answer so a=12 b=2 and c=11